Surfactant assisted formation of ruthenium nanochains under mild conditions and their catalytic CO oxidation activity - Sreedhala, S.; Vinod, C. P. (Chemical Communications, 2015)
Spontaneous formation of ruthenium nanochains is accomplished in aqueous medium under mild conditions using a seed mediated protocol with cetyl trimethylammonium bromide (CTAB) as the capping agent. They are formed due to the random self-assembly of Ru seeds of similar to 3.5 nm size. These 1D nanostructures exhibit better catalytic activity towards the oxidation of CO relative to the similar to 3.5 nmseeds and 6 nm Ru nanospheres. The synthesis strategy adopted here is found to be simple, facile and environmentally friendly.